ANALISIS RASIO KEUANGAN DALAM MENILAI KINERJA KEUANGAN DAERAH PEMERINTAH KOTA TEBING - Saragih, Fitriani; Siregar, Ilda Azilla (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2020, 2021)
The purpose of this study was to determine and analyze the financial performance of Tebing Tinggi City Government when viewed from the Regional Financial Independence Ratio, PAD Effectiveness Ratio, Regional Financial Efficiency Ratio, Harmony Ratio, and Growth Ratio.  This goal is motivated by the current condition in which local governments depend on subsidies from the central government which is reflected in the amount of central government assistance from the point of view of the routine budget.  The low ability of the regions to explore potential PAD sources, which is reflected in the relatively small acceptance of Regional Original Revenue (PAD) compared to total regional revenue, the lack of effort and the ability of regional revenue to manage and explore existing sources of income, the inefficiency of local governments in spending  area of research is quantitative descriptive research. The results of this study conclude that the ratio of independence is still very low, the effectiveness ratio of PAD is said to be good, the efficiency ratio is said to be bad, the compatibility ratio is said to be bad, the growth ratio is negative.